THE ISRAELI-IRANIAN RIVALRY AND THE QUEST FOR SUPREMACY IN THE MIDDLE EAST - Bidi Leila (International Conference on Social and Islamic Studies, 2021)
Iran and Israel had cultivated a close alliance during the Cold War 1947-1991. Their economic and military cooperation was based on prevalent interests and threats. Nevertheless, the 1979 Islamic Revolution was a watershed event in the history of their relationship. The end of the Cold War and the Iraqi defeat in the first Persian Gulf War resulted in a shift in the balance of power, in which many states in the region had emerged as regional competitors. Iran and Israel became rivals for prominence and leadership in the region. Their diplomatic and political relations have deteriorated recently, heightening the risk of escalation and direct military conflict. Israel perceives Iran as a threat to the existence of the Jewish state and its national security while Iranian leaders perceive Israel as a threat to their regional aspirations. This study explores the roots and origins of the long history of hostility between Iran and Israel. It provides a brief overview of the important factors that have shaped the Israeli-Iranian rivalry and demonstrates both states’ scramble for power and influence in the Middle East.